ANALISIS PERBEDAANABNORMAL RETURNSAHAM SEBELUM DAN SESUDAH PUTUSAN SIDANG SENGKETA PEMILU PRESIDEN 2014 (Studi Kasus Saham di Bursa Efek Indonesia) - Intan Ayu Rahmawati; Bety Nur Achadiyah (Jurnal Akuntansi Aktual, 2015)
Abstract: The purpose of this study was to determine the difference of abnormal stock returns before and after the Lawsuit Decision of Presidential Election in 2014.This study was conducted using event study. The population was all of the company’s financial data listed in the LQ-45 index at the Stock Exchangein 2014. The sampling method used in this research was purposive sampling and the number of sample used was 44 companies. The data used was secondary data taken from BEI. Data analysis technique used was paired sample t-test. The period of observation was 10 days before and 10 days after the events of the Lawsuit Decision of Presidential Election in 2014. Based on the results of t-test on the abnormal return in the period before and after the announcement showed that there was no significant difference between the average abnormal stock returns before and after the Lawsuit Decision of Presidential Election in 2014.Keywords: stock exchange, event study, abnormal return